2020
DOI: 10.1038/s41408-020-00349-4
|View full text |Cite
|
Sign up to set email alerts
|

Severe ineffective erythropoiesis discriminates prognosis in myelodysplastic syndromes: analysis based on 776 patients from a single centre

Abstract: The underlying mechanisms and clinical significance of ineffective erythropoiesis in myelodysplastic syndromes (MDS) remain to be fully defined. We conducted the ex vivo erythroid differentiation of megakaryocytic-erythroid progenitors (MEPs) from MDS patients and discovered that patient-derived erythroblasts exhibit precocity and premature aging phenotypes, partially by inducing the pro-aging genes, like ERCC1. Absolute reticulocyte count (ARC) was chosen as a biomarker to evaluate the severity of ineffective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…In accordance with this concept, multiple properties of the PD patients’ cells resembled aged HSCs, including the most markedly differentially overexpressed ribosomal gene set [ 42 ]. These data are also consistent with the concept of premature aging of MDS HSCs [ 74 ] and progenitors [ 75 ]. The non-cycling status and low replication rate signature were also associated with decreased expression of the replication-dependent histone genes of the HIST1 cluster, which are the most represented genes among the PD patients’ top 50 downregulated genes.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with this concept, multiple properties of the PD patients’ cells resembled aged HSCs, including the most markedly differentially overexpressed ribosomal gene set [ 42 ]. These data are also consistent with the concept of premature aging of MDS HSCs [ 74 ] and progenitors [ 75 ]. The non-cycling status and low replication rate signature were also associated with decreased expression of the replication-dependent histone genes of the HIST1 cluster, which are the most represented genes among the PD patients’ top 50 downregulated genes.…”
Section: Discussionsupporting
confidence: 91%
“…ARC (Absolute reticulocyte count) in peripheral blood was found to be a biomarker (when ARC < 20 × 10 9 /L) together with a shorter overall survival in the evaluation of the severity of ineffective erythropoiesis in 776 MDS patients. Huang et al concluded that the inadequate production of red blood cells in MDS may be partly due to premature ageing and apoptosis during erythroid differentiation as well as high-risk molecular genetic aberrations due to the altered expression of the ERCC1 gene [95].…”
Section: Myelodysplastic Syndromes (Mds)mentioning
confidence: 99%